Ответ:
![(x;y)=(5;4) (x;y)=(5;4)](https://tex.z-dn.net/?f=%28x%3By%29%3D%285%3B4%29)
Объяснение:
\left \{ {{2\sqrt{x+y} -3\sqrt{x-y} =3} \atop {9\sqrt{x+y} +3\sqrt{x-y} =30}} \right.=>11\sqrt{x+y}=33<=>\\<=>\sqrt{x+y}=3<=>x+y=9=>2* \sqrt{9} -3\sqrt{x-y}=3<=>\\<=>\sqrt{x-y}=1<=>x-y=1\\\left \{ {{x+y=9} \atop {x-y=1}} \right. =>(x;y)=(5;4)" alt="\left \{ {{2\sqrt{x+y} -3\sqrt{x-y} =3} \atop {3\sqrt{x+y} +\sqrt{x-y} =10}} \right. <=>\left \{ {{2\sqrt{x+y} -3\sqrt{x-y} =3} \atop {9\sqrt{x+y} +3\sqrt{x-y} =30}} \right.=>11\sqrt{x+y}=33<=>\\<=>\sqrt{x+y}=3<=>x+y=9=>2* \sqrt{9} -3\sqrt{x-y}=3<=>\\<=>\sqrt{x-y}=1<=>x-y=1\\\left \{ {{x+y=9} \atop {x-y=1}} \right. =>(x;y)=(5;4)" align="absmiddle" class="latex-formula">